Diagnostic maintenance management system for MV and HV substations - Smit, J.J; Ackerman, C.M (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
At many electric utilities, maintenance processes are changing by two major influences, which relate to market conditions and technical limitations, respectively. This paper describes how, on order to meet both of these challenges, KEMA has developed (in co-operation with the other Dutch utilities) a new diagnostic expert support system-based maintenance management methodology, called MainMan(R). (5 pages)